Analysis of Costs, Tariffs and Utilization of Increased Cost Recovery Rates - Ermi Girsang; Sri Lestari Ramadhani Nasution; Ibnu Rushd; Primanita Novi Andriati (Budapest International Research and Critics University, 2022)
Analysis of costs, tariffs and utilization of the Cost Recovery Rate (CRR) are important things to consider in providing health services. This study aims to analyze rates, costs and utilization in increasing CRR at Harapan Bunda Hospital. The type of research is quantitative and qualitative. The participants of this study were the Director, Head of Medical Services, Head of Finance, Head of Marketing, with 5 participants, quantitatively the samples taken were the top 5 diseases that were analyzed in 2019-2020. Collecting data with primary and secondary data, data were analyzed by reduction, data display and data verification. The results showed that there was a change in CRR every year, the method of determining service product rates and their comparison with competitor hospital rates in Batam, the number of patients with the disease, which amounted to 4222 people, only about 53 people were discharged dead for various reasons, the strategy adopted by the Harapan Bunda Hospital in increasing CRR is to promote several superior service products. The author suggests to further researchers using different methodologies, and to related staff and health workers to increase motivation and service quality, so as to make health care facilities to get better.